Post-consumer recycled colored polyethylene compositions, methods of manufacture thereof, and articles made therefrom - Patents.com

By performing multi-step treatment of regenerated mixed color polyethylene waste, a high-purity and low-pollution polyethylene mixed color composite material is prepared, which solves the problem of insufficient material purity and mechanical properties in the prior art, and realizes the production of high-performance regenerated materials suitable for a variety of application fields.

JP2025509989APending Publication Date: 2025-04-11BOREALIS AG
View PDF 11 Cites 0 Cited by

Patent Information

Application Number
JP2024556190
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Priority Date
2022-11-18
Filing Date
2023-03-20
Publication Date
2025-04-11

AI Technical Summary

Technical Problem

The prior art is difficult to produce regenerated PE-PCR materials with high purity, low pollution, consistent color and superior mechanical properties, especially in terms of toughness and environmental stress crack resistance under low temperature conditions.

Method used

High purity polyethylene mixed color composites are prepared by performing multi-step processing of regenerated mixed color polyethylene waste, including screening, sorting, washing and drying. The composition of this material includes more than 95.0% of d2-tetrachloroethylene soluble fraction, 73.0-91.0% of isoform multimer fraction, 10.0-22.0% of copolymer multimer fraction, and X-ray fluorescence spectroscopy to detect the heavy metal content below 100 ppm.

Benefits of technology

The production of high-purity polyethylene mixed color composite materials has been achieved, with high color consistency, low pollution, excellent mechanical properties and good environmental stress crack resistance, and is suitable for packaging, rotation molding, automobiles and cables.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2025509989000001
    Figure 2025509989000001
  • Figure 2025509989000002
    Figure 2025509989000002
  • Figure 2025509989000003
    Figure 2025509989000003
Patent Text Reader

Abstract

The present invention relates to a polymer having a melt flow rate of (i) 0.1 to 10 g / 10 min (ISO 1133, 5.0 kg; 190° C.); (ii) 950 to 990 kg / m 3 (iii) a density of at least 95.0% by weight of the d2 tetrachloroethylene soluble fraction (ISO 1183); 13 (iv) a homopolymer fraction (HPF) content, as measured according to chemical composition analysis by cross fractionation chromatography (CFC), in the range of 73.0 to 91.0 wt. %; (v) a copolymer fraction (CPF) content, as measured according to chemical composition analysis by cross fractionation chromatography (CFC), in the range of 10.0 to 22.0 wt. %; (vi) a total content of heavy metals selected from Cr, Cd, Hg and Pb, as measured by X-ray fluorescence (XRF), of less than or equal to 100 ppm, relative to the total polyethylene blend; and (vii) a full notch creep test (FNCT) time to failure, as measured according to ISO 16770-2019 at 50° C. and 6.0 MPa in 2 wt. % Arkopal N100, of at least 3.0 hours, wherein the polyethylene mixed color blend has an L of 30.0 to 73.0. * ;-10~25a * ;-5~20 b * of the CIELAB color space (L * a * b * The present invention also relates to a method for recycling polyethylene mixed color materials to obtain said blend, and to articles manufactured from said polyethylene mixed color blend.
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to mixed color polyethylene blends derived from post consumer recycled (PCR) materials. [Background technology]

[0002] The problem of disposal of accumulated plastic waste and the associated environmental problems have attracted widespread attention from the public and industry. Therefore, recycling of plastic materials has become an important topic, which can turn plastic waste into a valuable resource for new plastic products. Thus, in the recycling and reuse of plastic materials, environmental and economic aspects can be combined.

[0003] Recycling of plastic materials started already in the mid-1990s with the introduction of collection systems. Although collection systems allow a more targeted collection and separation of plastic materials from other household waste, the reuse of plastic materials derived from plastic waste is still limited. So-called post-consumer recycled (PCR) plastic materials generally contain a mixture of different plastics and some contaminants. Methods for further purification of post-consumer recycled (PCR) plastic materials are being developed.

[0004] Many attempts have been made to purify recycle streams derived from post-consumer plastic waste, including washing, sieving, aeration, distillation, etc. For example, WO 2018 / 046578 A1 discloses a method for producing polyolefin recycle from mixed color polyolefin waste, including packaging waste, comprising cold washing the waste with water, then washing with an alkaline medium at 60° C., followed by flake color sorting to obtain a color-sorted monopolyolefin-rich fraction.

[0005] US 5,767,230 A describes a method that involves contacting a PCR polyolefin chip containing volatile impurities with a heated gas at a superficial velocity sufficient to significantly reduce the volatile impurities, such as odor-active substances. However, so far contamination with residual benzene amounts has proven problematic. The origin of residual benzene in post-consumer recycled materials remains doubtful, but it represents an obstacle for end uses in areas such as medical packaging, food packaging, etc. Residual amounts of benzene, i.e. traces of benzene, are particularly problematic, since odor testing by olfactory experiments is not possible. End uses with specific requirements regarding odor are therefore excluded.

[0006] As a further problem, known recyclable materials suffer from moderate homogeneity as reflected in the surface contamination that occurs in injection molded articles. [Prior art documents] [Patent documents]

[0007] [Patent Document 1] WO 2018 / 046578 A1 [Patent Document 2] US 5,767,230 A Summary of the Invention [Problem to be solved by the invention]

[0008] Therefore, there remains a high demand for recycled materials with properties as close as possible to those of virgin resins.Specifically, the objective of the present invention is to provide a PE-PCR material that is superior to existing materials in that it has a higher product purity in terms of polyethylene content, a lower content of contaminants, a lighter shade of gray, a higher color consistency, better homogeneity, improved mechanical properties such as toughness performance even at low temperatures, good tensile and impact properties, and good processability.

[0009] The underlying objective of the present invention is to provide a post-consumer recycled polyethylene composition that addresses the above needs and shortcomings. [Means for solving the problem]

[0010] These objectives are achieved by the provision of a post-consumer recycled polyethylene composition that addresses the above needs and shortcomings.

[0011] Thus, the present invention provides (i) melt flow rate of 0.1–10 g / 10 min (ISO 1133, 5.0 kg; 190°C); (ii) 950-990 kg / m 3 density (ISO 1183); (iii) a d2 tetrachloroethylene soluble fraction in an amount of at least 95.0% by weight; 13 C2 fraction measured by C-NMR; (iv) homopolymer fraction (HPF) content, determined according to chemical composition analysis by cross fractionation chromatography (CFC), in the range of 73.0-91.0 wt.%; (v) copolymer fraction (CPF) content, determined according to chemical composition analysis by cross fractionation chromatography (CFC), ranging from 10.0 to 22.0 wt.%; (vi) a total content of heavy metals selected from Cr, Cd, Hg, and Pb, measured by X-ray fluorescence (XRF) as described herein, relative to the total polyethylene blend, of 100 ppm or less; and (vii) a time to failure in full notch creep test environmental stress crack resistance (FNCT) measured according to 16770-2019 at 50° C. and 6.0 MPa in 2 wt. % Arkopal N100 as described herein of at least 3.0 hours. A polyethylene mixed color blend having Polyethylene mixed color blends are 30.0~73.0L * ; -10~25a * ; -5~20b * of, The CIELAB color space (L * a * b * ) a polyethylene mixed color blend.

[0012] The above problem is further solved by the following steps: a) providing a mixed plastic waste stream (A); b) sieving the mixed plastic waste stream (A) to produce a sieved mixed plastic waste stream (B) containing only articles having a longest dimension in the range of 30-400 mm; c) classifying the sieved mixed plastic waste stream (B) by one or more classification systems equipped with near infrared (NIR) and optical sensors, whereby the sieved mixed plastic waste stream (B) is classified at least by polymer type and color and optionally article shape, thereby preparing a classified mixed color polyethylene recycle stream (CM) which is separately subjected to step d) and subsequent steps; d) shredding the classified mixed color polyethylene recycle stream (CM) to prepare a flaked mixed color polyethylene recycle stream (D); e) washing the flaked mixed color polyethylene recycle stream (D) with a first aqueous wash solution (W1) without input of thermal energy, thereby preparing a first suspension polyethylene recycle stream (E); f) removing at least a portion of the first aqueous wash solution (W1) from the first suspended polyethylene recycle stream (E) to obtain a first washed polyethylene recycle stream (F); g) washing the first washed polyethylene recycle stream (F) with a second aqueous washing solution (W2), thereby preparing a second suspension polyethylene recycle stream (G), wherein sufficient thermal energy is introduced into the second suspension polyethylene recycle stream (G) to provide a temperature in the range of 65-95°C during washing; h) removing the second aqueous wash solution (W2) and any material not suspended on the surface of the second aqueous wash solution (W2) from the second suspended polyethylene recycle stream (G) to obtain a second washed polyethylene recycle stream (H); i) drying the second washed polyethylene recycle stream (H), thereby obtaining a dried polyethylene recycle stream (I) comprising the polyethylene mixed color blend of the present invention. This is achieved by a method for recycling polyethylene mixed color materials, including:

[0013] The polyethylene mixed color blends of the present invention are obtainable or can be obtained by the above-described methods.

[0014] The present invention also provides articles made from the polyethylene mixed color blends of the present invention or obtained according to the above process.

[0015] The present invention further provides the use of the inventive polyethylene mixed color blends in packaging applications, rotational molding applications, automotive applications, or wire and cable applications. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0016] For the purposes of this specification and the claims that follow, the term "recycle stream" is used to denote materials that are processed from post-consumer waste, rather than virgin polymers and / or materials. Post-consumer waste refers to objects that have completed at least their first use cycle (or life cycle), i.e., have already fulfilled their initial purpose. The term "virgin" refers to newly produced materials and / or objects that have not yet been recycled and have not yet been used for the first time. The term "recycled material" as used herein refers to materials that have been reprocessed from post-consumer waste or recycling streams.

[0017] A blend is a mixture of two or more components, at least one of which is polymeric. In general, blends can be prepared by mixing two or more components. Suitable mixing procedures are known in the art. When such blends include virgin materials, the virgin materials are preferably polyethylene, comprising at least 90% by weight of reactor-produced polyethylene material, and optionally carbon black. Virgin materials are polymeric materials that have not yet been recycled.

[0018] For purposes of this specification and the claims that follow, the term "polyethylene mixed color blend" refers to a polymeric material that contains primarily ethylene-derived units, apart from other polymeric components of any nature, which may be derived, for example, from monomeric units derived from α-olefins such as propylene, butylene, octene, styrene derivatives such as vinylstyrene, substituted and unsubstituted acrylates, substituted and unsubstituted methacrylates.

[0019] The other polymeric material may be a material that is 13 The quantitative measurement used here and described in the subsequent measurement methods can be used to identify the color of the mixed polyethylene blends. 13 C{1H} NMR measurements allow the differentiation and quantification of various units in a polymer chain. These units are ethylene units (C2 units) and units with 3, 4, 6 or 7 carbon atoms. Thus, units with two carbon atoms (C2 units) can be differentiated in the NMR spectrum as consecutive C2 units and as isolated C2 units, indicating that the polymeric material comprises an ethylene-based polymer.

[0020] The polyethylene mixed color blends of the present invention typically contain small amounts of propylene-based polymer components, particularly small amounts of isotactic polyethylene (iPP) derived units, which, as described in the subsequent experimental section, contribute to the soluble fraction. 13 It can be measured by C-NMR analysis.

[0021] The term "C2 fraction" refers to a quantitative 13 C{ 1 It shows repeating ethylene-derived -[C2H4]- units present in the linear backbone and short chain branches as determined by {H} NMR spectroscopy, where repeat means at least two units.

[0022] The C2 fraction can be calculated as follows: wt C2画分 =fC 総C2 *100 / (fC 総C2 +fC PP ) Where: fC 総C2 =(Iddg-ItwoB4)+(IstarB1*6)+(IstarB2*7)+(ItwoB4*9)+(IthreeB5*10)+((IstarB4plus-ItwoB4-IthreeB5)*7)+(I3s*3) and fC PP =Isαα*3 Further details are given in the experimental section that follows.

[0023] In the recycled blends of the present invention, HDPE, LDPE, LLDPE, homo- and copolymer polyethylenes may be present. The polyethylenes can be characterized by analytical separation. A suitable method is chemical composition analysis by cross-fractionation chromatography (CFC). This method is described and successfully implemented by Polymer Char, Valencia Technology Par, Gustave Eiffel 8, Paterna E-46980 Valencia, Spain. Chemical composition analysis by cross-fractionation chromatography (CFC) allows fractionation into homopolymer fraction (HPF), copolymer fraction (CPF) and optionally present iso-PP fraction (IPPF). The homopolymer fraction (HPF) is a fraction that contains polyethylene similar to homopolymer HDPE. The copolymer fraction (CPF) is a component similar to polyethylene HDPE copolymers, but may also contain fractions of LDPE or LLDPE. The iso-PP fraction (IPPF) is defined as the polymer fraction that contains isotactic polypropylene and elutes at a temperature of 104°C or higher. The homopolymer fraction (HPF), the copolymer fraction (CPF) and any iso-PP fraction (IPPF) that is present add up to 100% by weight, which obviously means that the material is soluble in a cross fractionation chromatography (CFC) experiment.

[0024] The polyethylene blend of the present invention was analyzed for its chemical composition by cross fractionation chromatography (CFC) and the d2-tetrachloroethylene soluble fraction was also analyzed. 13 It is also characterized in that the amount of C2 fraction measured by C-NMR is at least 95.0% by weight, preferably at least 97.0% by weight. This percentage refers to the d2-tetrachloroethylene soluble portion used in the NMR experiments. The term "C2 fraction" corresponds to the polymer fraction obtained from ethylene monomer units rather than propylene monomer units.

[0025] The upper limit of the "C2 fraction" is 100% by weight.

[0026] Typically, in the polyethylene mixed color blends of the present invention, organic and inorganic fillers such as talc, chalk, carbon black, additional pigments such as TiO2, and additional ingredients such as paper and cellulose may be present.

[0027] The polyethylene mixed color blends of the present invention typically have a melt flow rate (ISO 1133, 5.0 kg; 190° C.) of 0.1 to 10 g / 10 min. The melt flow rate can be derived, for example but not limited to, from extended producer responsibility schemes such as the German DSD or influenced by the division of post-consumer plastic waste streams, which are separated from municipal solid waste into multiple pre-separated fractions and recombined in an appropriate manner. Preferably, the MFR5 is in the range of 0.5 to 5.0 g / 10 min, more preferably 0.7 to 4.0 g / 10 min, even more preferably 1.0 to 3.0 g / 10 min.

[0028] The polyethylene mixed color blend of the present invention has a viscosity of 950 to 990 kg / m 3 , preferably 955 to 987 kg / m 3 , more preferably 957 to 985 kg / m 3 of density measured in accordance with ISO 1183.

[0029] The polyethylene blends of the present invention have a d2-tetrachloroethylene soluble fraction in an amount of at least 95.0% by weight, preferably at least 97.0% by weight, more preferably at least 98.0% by weight. 13 It has a C2 fraction as measured by C-NMR.

[0030] Typically, the polyethylene blends of the present invention are recycled materials.

[0031] Typically, the nature of recycling can be assessed by the presence of one or more of the following: (1) Inorganic residue content greater than 0.1% by weight (as measured by TGA); Or in combination (2) 1 mg / m 3or more of limonene measured using a static headspace sampler coupled with a gas chromatograph and mass spectrometer (HS-GC-MS). It should be understood that option (2) is preferred.

[0032] Needless to say, the amount of inorganic residues, gels and limonene should be as low as possible.

[0033] The polyethylene mixed color blend of the present invention has a homopolymer fraction (HPF) content, as determined according to chemical composition analysis by cross fractionation chromatography (CFC), in the range of 73.0 to 91.0 wt%, preferably in the range of 75.0 to 90.0 wt%, more preferably in the range of 77.0 to 89.0 wt%, and even more preferably in the range of 79.0 to 88.0 wt%.

[0034] The polyethylene mixed color blend of the present invention has a copolymer fraction (CPF) content, as determined according to chemical composition analysis by cross fraction chromatography (CFC), in the range of 10.0 to 22.0 wt%, preferably in the range of 12.0 to 22.0 wt%, more preferably in the range of 13.0 to 21.0 wt%, and even more preferably in the range of 14.0 to 20.0 wt%.

[0035] The polyethylene mixed color blends of the present invention also have a total content of heavy metals selected from Cr, Cd, Hg and Pb, relative to the whole polyethylene blend, as measured by X-ray fluorescence (XRF) as described in the experimental section that follows, of 100 ppm or less, preferably 80 ppm or less, and more preferably 50 ppm or less.

[0036] The polyethylene mixed color blends of the present invention also exhibit a Full Notch Creep Test Environmental Stress Crack Resistance (FNCT) time to failure, measured in 2 wt. % Arkopal N100 at 50° C. and 6.0 MPa according to ISO 16770-2019 as described in the subsequent experimental section, of at least 3.0 hours, preferably at least 3.5 hours, more preferably at least 4.0 hours, and even more preferably at least 5.0 hours.

[0037] The polyethylene mixed color blends of the present invention also include 30.0~73.0L * ; -10~25a * ; -5~20b * , measured according to DIN EN ISO 11664-4 as described in the subsequent experimental paragraphs in the CIELAB color space (L * a * b * ).

[0038] Preferably, the CIELAB color space (L * a * b * )teeth, 32.0~71.0 L * ; -9~23a * ; -5~18b * It is defined by:

[0039] More preferably, the CIELAB color space (L * a * b * )teeth, 35.0~70.0L * ; -7~20a * ; -5~15b * It is defined by:

[0040] The polyethylene mixed color blends of the present invention are characterized by a higher chemical purity than conventional recycled materials, in particular a lower content of C3 units (propylene units) such as isotactic polypropylene (iPP). Preferably, the polyethylene mixed color blends of the present invention have a soluble fraction of 0.1-3.0 wt%, preferably 0.1-2.5 wt%, more preferably 0.2-2.0 wt%, as described in the subsequent experimental paragraph. 13 Contains units derived from isotactic polypropylene (iPP) as determined by C-NMR analysis.

[0041] The polyethylene mixed color blends of the present invention preferably have a large amplitude oscillatory shear-nonlinear index (LAOS-NLF) measured at 190°C, angular frequency of 0.628 rad / s, and strain of 1000%, as described in the experimental section that follows, in the range of 2.0 to 4.0.

[0042] LAOS-NLF:

number

[0043] LAOS-NLF also exhibits a nonlinear polymer structure: higher values ​​of LAOS-NLF indicate a higher content of long chain branches.

[0044] The polyethylene mixed color blends of the present invention preferably have a Shear Thinning Index (STF) value, defined as the ratio of the complex viscosities eta(0.05) to eta(300) at 190°C in the frequency range of 0.01 to 600 rad / s according to ISO 6721-1 and 6721-10, measured as described in the subsequent experimental paragraph, in the range of 30 to 60, more preferably in the range of 32 to 57, even more preferably in the range of 33 to 55. The Shear Thinning Index (STF) is indicative of the processability of the polyethylene material.

[0045] The polyethylene mixed color blends of the present invention preferably have a benzene content below the detection limit as measured by Static Headspace Chromatography Mass Spectrometry (HS / GC-MS) at 100°C / 2h as described in the experimental section that follows.

[0046] The polyethylene mixed color blends of the present invention preferably have an odor (VDA270-B3) of 5.0 or less, more preferably 4.0 or less. It should be understood that many commercially available recycle grades that have no reported odor are actually worse because they are prohibited from odor testing according to VDA270 due to the presence of problematic substances.

[0047] The polyethylene mixed color blends of the present invention preferably have a thermal conductivity of at least 5.0 kJ / m 2 , more preferably at least 5.5 kJ / m 2 , and even more preferably at least 6.0 kJ / m 2 of Charpy notched impact strength measured in accordance with ISO 179-1 eA at -20°C on injection moulded specimens of 80 x 10 x 4 mm made in accordance with EN ISO 1837-2.

[0048] The polyethylene mixed color blends of the present invention preferably have a tensile modulus, as described in the experimental section which follows, in the range of 600 to 1300 MPa, more preferably in the range of 700 to 1200 MPa, measured according to ISO 527-2.

[0049] The polyethylene mixed color blends of the present invention preferably have a flexural modulus, as described in the experimental section which follows, measured according to ISO 178, in the range of 600 to 1300 MPa, more preferably in the range of 700 to 1100 MPa.

[0050] The polyethylene mixed color blends of the present invention preferably have an impact strength of at least 3.0 m, more preferably at least 3.5 m, and even more preferably at least 4.0 m average drop height in a 1 L bottle drop test at 0° C. measured as described in the experimental section that follows, wherein the bottles are manufactured as described in the experimental section that follows.

[0051] The polyethylene mixed color blends of the present invention are preferably obtained from post-consumer recycled (PCR) materials, preferably 100% PCR material. Such PCR materials are typically obtained from consumer waste streams, such as waste streams generated in conventional collection systems (e.g., Extended Producer Responsibility, EPR, etc.) as implemented in the European Union. PCR materials may also come from municipal solid waste generated outside of the EPR collection system.

[0052] The raw materials for obtaining the polyethylene mixed color blends of the present invention may be selected from a wide range of fractions generated from municipal solid waste (MSW, often also referred to as residual waste, black bin waste) to Extended Producer Responsibility (EPR) based raw materials, for example the ARA 402 fraction from Altstoff Recycling Austria, the DSD 329 fraction from German producer responsibility organizations such as DSD-Duales System Holding, Interzero, Reclay, etc.

[0053] It is preferred that the polyethylene mixed color blends of the present invention are at least 95.0% by weight, more preferably at least 96% by weight, and even more preferably at least 97% by weight post-consumer derived.

[0054] The above object can also be achieved by the above polyethylene mixed color material recycling method, which includes the above steps a) to i). In other words, the polyethylene mixed color blend of the present invention is preferably obtained or has been obtained by the above method or the preferred method described below.

[0055] In step c), the sieved mixed plastic waste stream (B) may preferably be further classified by article shape, for example by type of use (MFR) or specific target using an artificial intelligence classification system (e.g. available from Tomra Systems, etc.). In the classification step c), the white and natural colored waste materials are preferably separated such that substantially only non-white and / or non-natural colored waste materials remain in the one or more classified mixed color polyethylene recycle streams (CM).

[0056] The sorting step c) preferably results in one or more sorted mixed color polyethylene recycle streams (CM). This can be achieved by removing preferably white and natural color polyethylene and non-polyethylene articles. In this specification, "natural" means that the article is naturally colored. It means that the article is essentially free of colorants such as dyes or inks or pigments (including carbon black). On the other hand, "white" refers to the inclusion of a white pigment in the article. The same logic applies to the sorting of flakes as described in step k) below. The term "mixed color" means that the particular material includes all colors except white and natural colors, which have been intentionally removed as much as possible.

[0057] In step f), preferably substantially all of the first aqueous wash solution (W1) is removed from the first suspension polyethylene polyolefin recycle stream (E) to obtain said first washed polyethylene recycle stream (F).

[0058] In step h), the removal of the second aqueous washing solution (W2) and the material not floating on the surface of the second aqueous washing solution is preferably achieved by a density separation step.

[0059] The method of the present invention may also further comprise at least one of the following steps: j) separating the dried polyethylene recycle stream (I) obtained in step i) into a light fraction and a heavy fraction polyethylene recycle stream (J); k) further classifying the heavy fraction polyethylene recycle stream (J) using an optical sorter with one or more NIR and / or optical sensors for the one or more target polyethylenes, or further classifying the dry polyethylene recycle stream (I) if step j) is not present, by removing flakes containing materials other than the one or more target polyethylenes or flakes of an undesirable color (e.g. black), thereby preparing a purified polyethylene recycle stream (K); l) melt extruding and preferably pelletizing the purified polyethylene recycle stream (K), wherein additives (Ad) are preferably added in the melt state to prepare an extruded, preferably pelletized, recycled polyethylene product (L); and m) introducing air into the recycled polyethylene product (L) or, in the absence of step l), into the purified polyethylene recycle stream (K) to remove volatile organic compounds, thereby preparing an aerated recycled polyethylene product (M), which is either an aerated extruded, preferably pelletized, recycled polyethylene product (M1) or an aerated recycled polyethylene flake (M2), wherein the order of steps l) and m) can be reversed so that air is first introduced into the purified polyethylene recycle stream (K) to prepare an aerated recycled polyethylene flake (M2), which is then extruded, in which additives (Ad) are preferably added in the molten state, to prepare an extruded, preferably pelletized, aerated recycled polyethylene product (M3), which is the polyethylene mixed color blend of the present invention.

[0060] In step j), separation may preferably be performed by air sieving, or may be performed based on the aerodynamic properties of the particles (e.g. flakes, e.g. separating thin, light and flexible flakes from heavy, thick and hard flakes).

[0061] After the above step j), a sieving step j1) may be carried out in which the dried polyethylene recycle stream (I) is sieved to remove fines to prepare a sieved polyethylene recycle stream (J1) which is then subjected to the above optional step k). In this sieving step j1), fines, preferably having a size of 2.5 mm or less, are removed.

[0062] The present invention is also directed to articles made from the polyethylene mixed color blends described above. The polyethylene blends of the present invention preferably comprise at least 85% by weight, more preferably at least 90% by weight, and even more preferably at least 93% by weight of the total composition for making the article. The remaining components may include additives such as antioxidants, stabilizers, colorants such as carbon black (optionally in the form of a masterbatch), pigments, dyes, or inks.

[0063] The article is preferably a bottle or other packaging article. The blends of the present invention may also be used in rotational molding applications, automotive applications, or wire and cable applications. In a preferred embodiment, the polyethylene blends of the present invention comprise in the range of 95% to 98% by weight of the total composition for making the article. Preferably, the article is made only from the polyethylene blends of the present invention and additives. The additives may preferably be selected from the group consisting of UV stabilizers, antioxidants, and / or acid scavengers.

[0064] The polyethylene mixed color blends of the present invention can also be blended with at least one virgin and / or recycled polyolefin, for example, virgin ethylene homopolymer or copolymer.

[0065] Measurement method The following definitions of terms and methods of measurement apply to the above general description of the invention and the following examples, unless otherwise indicated.

[0066] a) Melt flow rate Melt flow rate (MFR) is measured according to ISO 1133 and is given in g / 10 min. MFR is a measure of the flowability and therefore processability of a polymer. The higher the melt flow rate, the lower the viscosity of the polymer. Here, MFR is measured at a temperature of 190°C and under loads of 2.16 kg, 5.0 kg, or 21.6 kg.

[0067] b) Density Density was measured according to ISO 1183-1.

[0068] c) C2 fraction by NMR spectroscopy, and general microstructure including "continuous C3" and short chain branching quantitative 13 C{ 1 H}NMR spectrum. 1 H and 13 The NMR spectra were recorded in solution using a Bruker AVNEO 400 MHz NMR spectrometer operating at 400.15 and 100.62 MHz for C, respectively. 13 All spectra were recorded using a C optimized 10 mm extended temperature probe head. Approximately 200 mg of material was dissolved in approximately 3 mL of 1,2-tetrachloroethane-d2 (TCE-d2) along with approximately 3 mg of BHT (2,6-di-tert-butyl-4-methylphenol, CAS 128-37-0) and chromium-(III)-acetylacetonate (Cr(acac)3) to obtain a 60 mM solution of the relaxant in the solvent {singh09}. To ensure a homogenous solution, the NMR tube was further heated in a rotating furnace for at least 1 h after initial sample preparation in a heat block. Upon insertion into the magnet, the tube was spun at 10 Hz. Standard single pulse excitation was employed without NOE, using an optimized tip angle, a 1 second recycle delay, and a two-level WALTZ16 decoupling scheme {zhou07, busico07}. A total of 6144 (6k) transients were acquired per spectrum.

[0069] quantitative 13 C{ 1The {H} NMR spectra were processed, integrated, and relevant quantitative properties were derived from the integrals using a proprietary computer program. All chemical shifts were indirectly referenced to the central methylene group of the ethylene block (EEE) at 30.00 ppm using the chemical shift of the solvent. Characteristic signals corresponding to polyethylenes with different short chain branching (B1, B2, B4, B5, B6plus) and polyethylenes were observed {randall89, brandolini00}.

[0070] Characteristic signals were observed corresponding to the presence of polyethylene including isolated B1 branches (starB1 33.3 ppm), isolated B2 branches (starB2 39.8 ppm), isolated B4 branches (twoB4 23.4 ppm), isolated B5 branches (threeB5 32.8 ppm), all branches longer than 4 carbons (starB4plus 38.3 ppm), and the third carbon from the saturated aliphatic chain end (3s 32.2 ppm). 1 or other structural elements not observable are excluded from the equation. The intensities of polyethylene backbone carbons (dd 30.0 ppm), γ-carbons (g 29.6 ppm), 4s, and combined ethylene backbone methine carbons (ddg) including three B4 carbons (corrected later) are measured between 30.9 ppm and 29.3 ppm, excluding Tββ from polyethylene. The amount of C2-related carbons is calculated according to the following formula: fC 総C2 =(Iddg-ItwoB4)+(IstarB1*6)+(IstarB2*7)+(ItwoB4*9)+(IthreeB5*10)+((IstarB4plus-ItwoB4-IthreeB5)*7)+(I3s*3) All the aforementioned signals were quantified according to the method described above.

[0071] Where characteristic signals corresponding to the presence of polyethylene (PP, continuous C3) were observed at 46.7 ppm, 29.0 ppm, and 22.0 ppm, the amount of PP-associated carbon was quantified using the integral of Sαα at 46.6 ppm. fC PP =Isαα*3

[0072] The weight percent of the C2 fraction and polyethylene is calculated according to the following formula: wt C2画分 =fC 総C2 *100 / (fC 総C2 +fC PP ) wt PP =fC PP *100 / (fC 総C2 +fC PP ) It can be quantified according to

[0073] Characteristic signals corresponding to various short chain branches were observed and their weight percentages were quantified starting from quantifying the weight fraction of each, such that the relevant branches were α-olefins. fwtC2=fC 総C2 -(IstarB1*3)-(IstarB2*4)-(ItwoB4*6)-(IthreeB5*7) fwtC3(isolated C3)=IstarB1*3 fwtC4=IstarB2*4 fwtC6=ItwoB4*6 fwtC7=IthreeB5*7

[0074] All weight percentages are normalized to give weight percent amounts of all relevant branches. fsum 総重量% =fwtC2+fwtC3+fwtC4+fwtC6+fwtC7+fCPP wtC2=fwtC2*100 / fsum 総重量% wt total C3=fwtC3*100 / fsum 総重量% wt total C4=fwtC4*100 / fsum 総重量% wtC6=fwtC6*100 / fsum 総重量% wt total C7=fwtC7*100 / fsum 総重量%

[0075] zhou07 Zhou, Z., Kuemmerle, R., Qiu, X., Redwine, D., Cong, R., Taha, A., Baugh, D. Winniford, B., J. Mag. Reson. 187 (2007) 225 busico07 Busico, V., Carbonniere, P., Cipullo, R., Pellecchia, R., Severn, J., Talarico, G., Macromol. Rapid Commun. 2007, 28, 1128 singh09 Singh, G., Kothari, A., Gupta, V., Polymer Testing 28 5 (2009), 475 randall89 J. Randall, Macromol. Sci., Rev. Macromol. Chem. Phys. 1989, C29, 201. brandolini00 AJ Brandolini, DD Hills, NMR Spectra of Polymers and Polymer Additives, Marcel Dekker Inc., 2000c) Crystex analysis, crystalline fraction (CF) and soluble fraction (SF)

[0076] d) Cross-fractionation chromatography The chemical composition distribution, as well as the molecular weight distribution and the corresponding molecular weight averages (Mn, Mw and Mv) at specific elution temperatures (polymer crystallinity in solution) were determined by fully automated cross-fractionation chromatography (CFC) as described in Ortin A., Monrabal B., Sancho-Tello J., Macromol. Symp., 2007, 257, 13-28.

[0077] A CFC instrument (PolymerChar, Valencia, Spain) was used to perform cross-fractionation chromatography (TREF x SEC). A 4-band IR5 infrared detector (PolymerChar, Valencia, Spain) was used to monitor the concentration. The polymer was dissolved at 160°C for 150 min at a concentration of approximately 1 mg / mL.

[0078] To avoid injection of possible gels and polymers that are not soluble in TCB at 160° C., such as PET and PA, a weighed sample was packed into a stainless steel mesh of MW 0.077 / D 0.05 mmm.

[0079] Once the sample was completely dissolved, 0.5 mL aliquots were loaded onto a TREF column and stabilized at 110° C. for a period of time. A constant cooling rate of 0.1° C. / min was applied to reach a temperature of 30° C. to crystallize and precipitate the polymer. A discontinuous elution process is carried out using the following temperature steps: (35, 40, 50, 55, 60, 65, 70, 75, 80, 85, 90, 95, 100, 103, 106, 109, 112, 115, 117, 119, 121, 123, 125, 127, 130, 135 and 140).

[0080] In the second dimension, a 3 PL Olexis column and 1x Olexis Guard column from Agilent (Church Stretton, UK) were used as stationary phase in the GPC analysis. As eluent, 1,2,4-trichlorobenzene (TCB, stabilized with 250 mg / L of 2,6-di-tert-butyl-4-methylphenol) was applied at a constant flow rate of 1 mL / min at 150 °C. The column set was calibrated using a universal calibration (according to ISO 16014-2:2003) using at least 15 narrow MWD polystyrene (PS) standards ranging from 0.5 kg / mol to 11500 kg / mol. The following Mark Houwink constants were used to convert PS molecular weights to PP molecular weight equivalents: K PS =19×10 -3 mL / g, α PS =0.655 K PP =19×10 -3 mL / g, α PP =0.725

[0081] A third order polynomial fit was used to fit the calibration data. Data processing was performed using software provided by PolymerChar in conjunction with the CFC instrument.

[0082] e) Environmental Stress Crack Resistance (FNCT) Environmental stress crack resistance is evaluated by full notch creep testing (FNCT). FNCT failure time was measured according to the full notch creep test method (FNCT) ISO 16770-2019 at 50 °C using a notch depth of 1 mm and specimen dimensions 6 mm × 6 mm × 90 mm (4 mm × 4 mm). The solvent used was 2 wt% Arkopal N100 in deionized water. Sample preparation was performed according to ISO 16770-2019 (compression molding and annealing).

[0083] The specimens were subjected to a stress of 6.0 MPa in aqueous solution. Three to four specimens were tested for each sample. The average time to failure of all measurements was used to report the time to failure in hours.

[0084] f) Bottle drop test 1 L bottles with an outer diameter of 90 mm, a wall thickness of 0.6 mm, an overall height of 204 mm and a cylindrical mantle height of 185 mm were produced by extrusion blow moulding on a B&W machine equipped with a single screw extruder at a melt temperature of 190°C and a mould temperature of 15°C as described in WO 2020 / 148319 A1.

[0085] The stepwise drop test was carried out as described in WO 2020 / 148319 A1. Each bottle as defined above is dropped several times in succession from increasing heights. The test is stopped for each bottle when breakage occurs.

[0086] Drop tests are performed on extrusion blow molded 1 L bottles, as described above, filled to the shoulder with water.

[0087] Each test series requires at least 12 bottles. Four bottles are dropped simultaneously from a starting height selected according to the table below. The expected breaking drop height has been measured in a pre-test or selected from experience.

[0088] TIFF2025509989000002.tif15135

[0089] Any bottles showing failure are discarded and the test continues with the remaining bottles, increasing in height. The width of the increase in height step depends on the starting height. If the starting height is less than 0.5m, the step width is 0.1m, but if the starting height is 0.5m or more, the step width is 0.25m. The failure drop height of each bottle is recorded and the average failure drop height is calculated from the individual values ​​according to the following formula:

number

[0090] g) Tensile modulus and tensile strain at break The tensile modulus and tensile strain at break were determined according to ISO 527-2 (crosshead speed = 1 mm / min, test speed 50 mm / min at 23 °C) using injection-molded specimens (dogbone shape, thickness 4 mm) as described in EN ISO 1873-2. The measurements are carried out after conditioning the specimens for 96 hours.

[0091] h) Flexural modulus Flexural modulus was measured according to ISO 178 Method A (3-point bending test) on 80 mm x 10 mm x 4 mm. According to the standard, a test speed of 2 mm / min and a span length of 16 x thickness were used. The test temperature was 23 ± 2°C. Injection moulding was carried out according to ISO 17855-2.

[0092] i) Impact strength (Charpy NIS) Impact strength was measured as notched Charpy impact strength (1 eA) according to ISO 179-1 eA (non-instrumented, ISO 179-1 at 0 °C) at +23 °C and -20 °C on 80 × 10 × 4 mm injection-molded specimens prepared according to EN ISO 1873-2.

[0093] j) CIELAB color space (L * a * b * ) CIE L * a * b * In the uniform color space, the color coordinates are as follows: * is the brightness coordinate, a * is the red / green coordinate (+a * is red, -a * indicates green), b * is the yellow / blue coordinate (+b * is yellow, -b * indicates blue). * , a * , b * The coordinate axes define the three-dimensional CIE color space. Standard Konica / Minolta colorimeter CM-3700A.

[0094] k) Heavy metal content The contents of heavy metals including Cr, Cd, Hg and Pb were measured by X-ray fluorescence (XRF). The instrument used for the XRF measurements was a Malvern Panalytical wavelength dispersive Zetium (2.4 kW). The instrument was calibrated using a set of polyolefin-based standards manufactured by Malvern Panalytical, namely Toxel. The analysis is carried out under vacuum on plaques 40 mm in diameter and 2 mm thick. This method is used to determine the quantitative content of Cr, Cd, Hg and Pb in a polyolefin matrix within the ranges defined in this standard.

[0095] l) Headspace gas chromatography / mass spectrometry (HS-GC-MS) The determination of benzene and limonene is based on the static headspace (HS) approach, which uses a HS sampler coupled with a gas chromatograph (GC) and mass spectrometer (MS) for screening purposes. Samples were delivered to the laboratory in sealed aluminum-coated polyethylene (PE) bags. Prior to analysis, samples were ground in a cryomill and 2.000 ± 0.100 g were weighed into 20 mL HS vials and tightly sealed. Duplicate measurements were performed for each sample.

[0096] 1.1 HS / GC / MS parameters HS parameters (Agilent G1888 headspace sampler) Vial equilibration time: 120 minutes (sample), 5 minutes (standard) Furnace temperature: 100℃ (sample), 200℃ (standard) Loop temperature: 110℃ (sample), 205℃ (standard) Transfer line temperature: 120℃ (sample), 210℃ (standard) low vibration GC parameters (Agilent 7890A GC system) Column: ZB-WAX 7HG-G007-22 (30m x 250μm x 1μm) Carrier gas: Helium 5.0 Flow: 2mL / min Split: 5:1 GC furnace program: 0.1 min at 35°C 10℃ / min up to 250℃ 250℃ 1 minute MS parameters (Agilent 5975C Insert XL MSD) Acquisition mode: Scan Scan parameters: Low mass: 20 High mass: 200 Threshold: 10 Software / Data Evaluation MSD ChemStation E.02.02.1431 MassHunter GC / MS Acquisition B.07.05.2479 AMDIS GC / MS Analysis Version 2.71 NIST / EPA / NIH Mass Spectral Library (2011 Version) NIST Mass Spectral Search Program Version 2.0g · AMDIS Deconvolution Parameters Minimum Match Factor: 80 Threshold: Low Scan Direction: High to Low Data File Format: Agilent File Instrument Type: Quadrupole Configuration Width: 20 Adjacent Peak Subtraction: 2 Resolution: High Sensitivity: Very High Shape Requirement: Medium Solvent Tailoring: 91 m / z Column Bleed: 207 m / z Min. Model Peaks: 2 Min. S / N: 10 Min. Specific Peaks: 0.5 · MSD ChemStation Integration Parameters Integrator: ChemStation Initial Area Reject: 0 Initial Peak Width: 0.005 Shoulder Detection: Off Initial Threshold: 10.5

[0097] In this study, the description "below the limit of detection (<LOD)" means that the match factor is less than 80 (AMDIS) or the signal-to-noise ratio of the peak in the sample run (Pk-pk S / N = corrected signal / Pk-pk noise, MSD ChemStation signal-to-noise report) is less than 3. The results refer only to the measured sample, measurement time, and applied parameters.

[0098] 1.2 Standard Solution For positive identification and comparison with the (lowest) odor detection thresholds (ODTs), benzene and limonene standards, respectively, were used (see Table 1). For HS / GC / MS analysis, 5 μL of each standard was injected into a 20 mL HS vial, tightly sealed and measured. Assuming complete evaporation of the standard, HSc G The concentrations of benzene (or limonene in other cases) in the samples were estimated as shown in Table 1.

[0099] TIFF2025509989000004.tif26139

[0100] 1.3 Data Evaluation HSc G The concentration of the analyte in the G and the available HS volume V G It is calculated taking into account (Equation 1).

number

[0101] To estimate the concentration of the analyte in the HS above the polymer sample, the response factor Rf of a one-point calibration is required (Eq. 2). The peak area of ​​the analyte is obtained by integrating the extracted ion chromatogram (EIC). The corresponding target ion is shown in.

number

[0102] Concentration of the analyte in the HS above the polymer sample, c G 試料 is calculated by multiplying the response factor and the EIC peak area of ​​the sample (Equation 3).

number

[0103] In addition, the odor relevance of the analyte in the HS above the polymer sample is estimated by the odor activity value (OAV). Therefore, the concentration of the analyte in the HS above the polymer sample, c G 試料 is compared to the (lowest) odor detection threshold (ODT) reported in the literature (Eq. 4) [1]. Values ​​above 1 indicate the odor relevance of the analyte at a particular HS temperature.

number

[0104] 1.4 Considerations and Limitations It has to be taken into account that the ODT of some substances is below the limit of detection (LOD) of the method, therefore components below the LOD may be missed, although they are associated with the overall odor.

[0105] OAV is based on the assumption that the HS parameters are to some extent related to the measurement conditions of the ODT measurement. Of course, this cannot be fully applied since a temperature setting of 100 °C is not always chosen in such experiments and is therefore limited to practical values. Nevertheless, this approach can at least indicate the odor relevance of a given marker substance.

[0106] Considering all the aforementioned assumptions and limitations, the measured concentrations at the HS above the samples, and the odor activity values ​​should be treated as estimates only.

[0107] 1.5 References [1]Van Gemert LJ, Odour Thresholds: Compilations of odour threshold values ​​in air, water and other media, Utrecht, Oliemans Punter & Partners BV, 2011.

[0108] n) Odor (VDA270-B3) VDA270 measures the odor characteristics of automotive interior materials. In this study, odor is measured according to VDA270 (2018) variant B3. Each assessor evaluates the odor of each sample according to the VDA270 scale, opening the jar lid as little as possible. The six evaluation scales consist of the following grades: Grade 1: not perceptible, Grade 2: perceptible but not intrusive, Grade 3: clearly perceptible but not intrusive, Grade 4: intrusive, Grade 5: strongly intrusive, Grade 6: unacceptable. The assessors must remain calm during the evaluation and are not allowed to prejudice each other by discussing their individual results during the test. They are also not allowed to adjust these evaluations after testing another sample. For statistical reasons (and as allowed by VDA270), the assessors are forced to employ the entire process in the evaluation. As a result, the odor grade is based on the average of all individual evaluations, rounded to an integer.

[0109] o) Dynamic rheology measurements Characterization of polymer melts by dynamic shear measurements follows ISO standards 6721-1 and 6721-10. Measurements were performed on an Anton Paar MCR501 stress-controlled rotational rheometer with a 25 mm parallel plate geometry. Measurements were performed on compression molded plates using a nitrogen atmosphere and strains set within the linear viscoelastic region. Oscillatory shear tests were performed at 190 °C and 200 °C for PE and PP, respectively, applying a frequency range of 0.01-600 rad / s and setting the gap at 1.3 mm. In dynamic shear experiments, the probe is subjected to uniform deformation with sinusoidally varying shear strain or shear stress (strain-controlled and stress-controlled modes, respectively). In controlled strain experiments, the probe is subjected to the following: (t) = γ0 sin(ωt) (1) The sinusoidal distortion may be expressed as: If the applied strain is within the linear viscoelastic region, the resulting sinusoidal stress response is: (t) = σ0 sin(ωt + δ) (2) It can be expressed as: In the above formula, σ0 and γ0 are the stress and strain amplitudes, respectively; ω is the angular frequency, δ is the phase shift (loss angle between the applied strain and the stress response) where t is time.

[0110] The results of dynamic testing are usually expressed in terms of several different rheological functions, namely, the shear storage modulus G', the shear loss modulus G", the complex shear modulus G, and the shear loss modulus G. * , complex shear viscosity η * , the dynamic shear viscosity η', the out-of-phase components of the complex shear viscosity η", and the loss tangent tanδ It is expressed by:

number

[0111] The so-called shear thinning index (STF) is measured as shown in the following formula (9).

number

[0112] The values ​​are measured by a single-point interpolation procedure defined in the Rheoplus software. * In situations where values ​​were not achieved experimentally, the values ​​were determined by extrapolation using the same procedure as before. In both cases (interpolation or extrapolation), the Rheoplus options "Interpolate y values ​​from parameters to x values" and "Logarithmic interpolation type" were applied.

[0113] These tests were performed on compression molded disks using cryomilled powder.

[0114] p) LAOS nonlinear viscoelasticity ratio The nonlinear viscoelastic behavior under shear flow was investigated by large amplitude oscillatory shear. This method requires the application of a sinusoidal strain amplitude γ0 at a given angular frequency ω for a given time t. If the applied sinusoidal strain is large enough, a nonlinear response will occur. In this case, the stress σ is a 20 function of the applied strain amplitude, time and angular frequency. Under these conditions, the nonlinear stress response is still a periodic function, but can no longer be expressed by a single harmonic sinusoid. The stress resulting from the nonlinear viscoelastic response [0-0] can be expressed by a Fourier series including the contributions of higher harmonics.

number

[0115] The nonlinear viscoelastic response was analyzed by applying large amplitude oscillatory shear (LAOS) [4-6]. Time sweep measurements were performed using an Alpha Technologies RPA 2000 rheometer coupled with a standard biconical die. During the measurements, the test chamber is sealed and a pressure of approximately 6 MPa is applied. LAOS tests are performed at a temperature of 190 °C, an angular frequency of 0.628 rad / s, and a strain of 1000%. To ensure that a steady state is reached, the nonlinear response is measured after at least 20 cycles are completed per measurement. The large amplitude oscillatory shear nonlinearity index (LAOS-NLF) is given by:

number

[0116] These tests were carried out on cryomilled powders. [1] J. M. Dealy, K. F. Wissbrun, Melt Rheology and Its Role in Plastics Processing: Theory and Applications; edited by Van Nostrand Reinhold, New York (1990) [2] S. Filipe, Non-Linear Rheology of Polymer Melts, AIP Conference Proceedings 1152, pp. 168-174 (2009) [3] M. Wilhelm, Macromol. Mat. Eng. 287, 83-105 (2002) [4] S. Filipe, K. Hofstadler, K. Klimke, A. T. Tran, Non-Linear Rheological Parameters for Characterisation of Molecular Structural Properties in Polyolefins, Proceedings of Annual European Rheology Conference, 135 (2010) [5] S. Filipe, K. Klimke, A. T. Tran, J. Reussner, Proceedings of Novel Non-Linear Rheological Parameters for Molecular Structural Characterisation of Polyolefins, Novel Trends in Rheology IV, Zlin, Check Republik (2011) [6] K. Klimke, S. Filipe, AT Tran, Non-Linear rheological parameters for characterization of molecular structural properties in polyolefins, Proceedings of European Polymer Conference, Granada, Spain (2011)

[0117] q) Inorganic residues The inorganic residues were determined by TGA according to DIN ISO 1172:1996 using a Perkin Elmer TGA 8000. Approximately 10-20 mg of material was introduced into a platinum dish. The temperature was equilibrated at 50°C for 10 min and then increased to 950°C under nitrogen at a heating rate of 20 / °C min. The ash content was evaluated at 850°C as % by weight. EXAMPLES

[0118] The raw material for IE1 was obtained from mixed plastic fractions sorted from municipal solid waste (MSW) in Greece and Poland.

[0119] The raw material for IE2 was obtained from polyethylene sorted from post-consumer waste (PCW) multi-layer milk bottles sourced commercially available on the French and Swiss markets.

[0120] CE1 is a commercially available HDPE recycled material. It is based on a post-consumer waste (PCW) feedstock, which mainly consists of pre-sorted municipal waste.

[0121] The HDPE mixed recycled material for compositions IE1 and IE2 is processed by the following process: a) providing a post-consumer plastic waste fraction (as identified above) in a bale; b) sieving the material to remove small fractions (and optionally large fractions); c) A color sorting process using near infrared (NIR) and optical sensors to classify white and transparent / natural colors (e.g. white bottles, transparent shampoo bottles, yogurt cups, etc.) and classify other polymer types (PP, PS, PA) and contaminants such as paper, wood, etc.; d) crushing the remaining fraction consisting of colored HDPE articles, washing with an alkaline aqueous solution containing various detergents, followed by drying, air sieving and sieving; e) further classifying the resulting plastic flake material to remove non-polyolefin flakes; f) extruding the material to obtain the HDPE blend according to the invention as pellets. The resulting mixture was recycled using a method including the steps of:

[0122] The properties of the resulting recycled polyethylene mixed color blend are shown in Table 1 below.

[0123] [Table 1-1]

[0124] [Table 1-2]

[0125] The above mentioned IE1, IE2 and CE1 samples were subjected to environmental stress crack resistance according to the FNCT test according to ISO 16770-2019 at 50 °C and 6.0 MPa in 2 wt% Arkopal N100 and impact strength by the bottle drop test described in the experimental section, the results are shown in Table 2 below.

[0126] [Table 2]

[0127] The results show that IE1 and IE2 polyethylene mixed color blends improved commercial recyclables in various properties, including: - (Very) high purity of rHDPE mixed recycled material (low amount of iPP); -No detection of benzene by HS GC-MS; - (very) low concentrations of pollutants from heavy metals (Cr, Cd, Pb, Hg); -Excellent toughness performance (Charpy notched impact strength) even at low temperatures; -Good mechanical performance of the bottle (e.g. bottle drop test); -Improved resistance to environmental stress cracking (FNCT).

[0128] An improvement in chemical purity is shown by IE1 with an iPP content of only 0.8 wt. %. In contrast, the conventional recycle from CE1 had 12.1 wt. % impurities. At the same time, both examples IE1 and IE2 showed low concentrations of heavy metals and benzene contents below the detection limit. This requirement was not met by CE1.

[0129] The mixed color blends of IE1 and IE2 showed improved mechanical performance over the blend of CE1. Both inventive examples showed excellent Charpy notched impact strength (Table 1), excellent ESCR (FNCT) and toughness in bottle drop test (Table 2).

Claims

1. (i) a melt flow rate of 0.1 to 10 g / 10 min (ISO 1133, 5.0 kg; 190° C.); (ii) 950-990kg / m 3 density (ISO 1183); (iii) a d2 tetrachloroethylene soluble fraction in an amount of at least 95.0% by weight; 13 C2 fraction measured by C-NMR; (iv) a homopolymer fraction (HPF) content, as determined according to chemical composition analysis by cross fractionation chromatography (CFC), in the range of 73.0 to 91.0 wt.%; (v) a copolymer fraction (CPF) content, determined according to chemical composition analysis by cross fractionation chromatography (CFC), ranging from 10.0 to 22.0 wt. %; (vi) a total content of heavy metals selected from Cr, Cd, Hg, and Pb, measured by X-ray fluorescence (XRF) as described herein, relative to the total polyethylene blend, of 100 ppm or less; and (vii) a time to failure in a full notch creep test (FNCT) measured in 2 wt. % Arkopal N100 as described herein at 50° C. and 6.0 MPa according to ISO 16770-2019 of at least 3.0 hours. having L 30.0 to 73.0 * ; -10 to 25 a * ; -5 to 20 b * of, CIELAB color space (L * a * b * ) Polyethylene mixed color blend.

2. of the soluble fraction as described herein. 13 2. The polyethylene mixed color blend of claim 1, having 0.1 to 3.0 wt. % of isotactic polypropylene (iPP) derived units as determined by C-NMR analysis.

3. Large Amplitude Oscillatory Shear-Nonlinear Index (LAOS-NLF) measured at 190° C., angular frequency 0.628 rad / s, and strain 1000% as described herein: [0010] [In the formula, G 1 ' is the first Fourier coefficient, and G 3 ' are the third-order Fourier coefficients. The polyethylene mixed color blend of claim 1 or 2, wherein the β-

4. The polyethylene mixed color blend according to any of claims 1 to 3, wherein the Shear Thinning Index (STF) value, defined as the ratio of complex viscosities eta(0.05) to eta(300) at 190°C in the frequency range of 0.01 to 600 rad / s according to ISO 6721-1 and 6721-10, measured as described herein, is in the range of 30 to 60.

5. The polyethylene mixed color blend according to any one of claims 1 to 4, having a benzene content below the detection limit as measured by Static Headspace Chromatography Mass Spectroscopy (HS / GC-MS) at 100°C / 2hrs as described herein.

6. The Charpy notched impact strength measured according to ISO 179-1 eA at -20°C on 80 x 10 x 4 mm injection moulded specimens prepared according to EN ISO 1873-2 is at least 5.0 kJ / m 2 The polyethylene mixed color blend of any one of claims 1 to 5,

7. 7. The polyethylene mixed color blend of any of claims 1 to 6, having an impact strength of at least 3.0 meters average drop height in a 1 L bottle drop test as described herein at 0° C., wherein the bottle is manufactured as described herein.

8. a) providing a mixed plastic waste stream (A); b) sieving the mixed plastic waste stream (A) to produce a sieved mixed plastic waste stream (B) containing only articles having a longest dimension in the range of 30-400 mm; c) classifying the sieved mixed plastic waste stream (B) by one or more classification systems equipped with near infrared (NIR) and optical sensors, whereby the sieved mixed plastic waste stream (B) is classified at least by polymer type and color and optionally article shape, thereby preparing a classified mixed color polyethylene recycle stream (CM) which is separately subjected to step d) and subsequent steps; d) shredding the classified mixed color polyethylene recycle stream (CM) to prepare a flaked mixed color polyethylene recycle stream (D); e) washing the flaked mixed color polyethylene recycle stream (D) with a first aqueous wash solution (W1) without input of thermal energy, thereby preparing a first suspension polyethylene recycle stream (E); f) removing at least a portion of the first aqueous wash solution (W1) from the first suspended polyethylene recycle stream (E) to obtain a first washed polyethylene recycle stream (F); g) washing the first washed polyethylene recycle stream (F) with a second aqueous wash solution (W2), thereby preparing a second suspension polyethylene recycle stream (G), wherein sufficient thermal energy is introduced into the second suspension polyethylene recycle stream (G) to provide a temperature in the range of 65-95° C. during washing; h) removing the second aqueous wash solution (W2) and any material not suspended on the surface of the second aqueous wash solution (W2) from the second suspended polyethylene recycle stream (G) to obtain a second washed polyethylene recycle stream (H); i) drying the second washed polyethylene recycle stream (H) thereby obtaining a dried polyethylene recycle stream (I) comprising the polyethylene mixed color blend according to any one of claims 1 to 7. A method for recycling a polyethylene mixed color material comprising:

9. The following steps: j) separating the dried polyethylene recycle stream (I) obtained in step i) into a light fraction and a heavy fraction polyethylene recycle stream (J); k) further classifying the heavy fraction polyethylene recycle stream (J), or, in the absence of step j), further classifying the dry polyethylene recycle stream (I), using one or more optical classifiers to classify the one or more target polyethylenes by removing flakes containing materials other than the one or more target polyethylenes, thereby preparing a purified polyethylene recycle stream (K); l) melt extruding and preferably pelletizing the purified polyethylene recycle stream (K) to prepare an extruded, preferably pelletized, recycled polyethylene product (L), preferably with the addition of additives (Ad) in the molten state; and m) introducing air into the recycled polyethylene product (L) or, in the absence of step l), into the purified polyethylene recycle stream (K) to remove volatile organic compounds, thereby preparing an aerated recycled polyethylene product (M), which is either an aerated extruded, preferably pelletized recycled polyethylene product (M1) or an aerated recycled polyethylene flake (M2); 9. The method of claim 8, further comprising at least one of: The order of steps l) and m) can be reversed, such that air is first introduced into a purified polyethylene recycle stream (K) to prepare aerated recycled polyethylene flakes (M2) which are then extruded, in which an additive (Ad) is preferably added in the molten state to prepare an extruded, preferably pelletized, aerated recycled polyethylene product (M3), which is a polyethylene mixed color blend according to any one of claims 1 to 7.

10. A polyethylene mixed colour blend according to any of claims 1 to 7, obtainable or obtained by the process according to claim 8 or 9.

11. An article made from the polyethylene mixed color blend of any of claims 1-7 or 10.

12. 12. The article of claim 11, which is a bottle.

13. A blend comprising the polyethylene mixed color blend of any of claims 1 to 7 or 10 and at least one virgin polyolefin and / or recycled polyolefin.

14. 11. Use of the polyethylene mixed color blend of any of claims 1 to 7 or 10 in packaging applications, rotational molding applications, automotive applications, or wire and cable applications.

Citation Information

Patent Citations

  • A processing line for recycling plastics

    GB2465839A

  • Method and apparatus for sorting plastic articles

    JP1994506149A

  • Skin layer for power or communication cables

    JP2008544469A

  • Process for manufacturing high-density polyethylene compound

    JP2016507601A

  • Multimodal polymer

    JP2016538397A